Principles of microeconomics - Bernanke, B.; Antonovics, K.; Heffetz, O. (New York : McGraw Hill LLC, 2022)
"lthough many millions of dollars are spent each year on introductory economics instruction in American colleg-es and universities, the return on this investment has been disturbingly low. Studies have shown, for example, that several months after having taken a principles of economics course, former students are no better able to answer simple economics questions than others who never even took the course. Most students, it seems, leave our introductory courses without having learned even the most important basic economic principles"--
Includes glossary and index.
Keywords: Microeconomics